Improving undergraduates' argumentative group essay writing through self-assessment - Yong, Mei Fung; Hooi, Chee Mei (Australian International Academic Centre, 2015)
When writing an argumentative essay, writers develop and evaluate arguments to embody, initiate, or simulate various kinds of interpersonal and textual interaction for reader consideration (Wu & Allison, 2003). This is quite challenging for English as a second language (ESL) learners. To improve the quality of their writing, students need to review their draft throughout the writing process. This study aimed to investigate the effect of self-assessment in group writing and how group work improves students’ writing ability. An intact class comprising 22 first-year undergraduates participated in the study. Data were collected from pre- and post-treatment writing tests, semi-structured interview and reflection entries. The results revealed that self-assessment has a significant effect on students’ writing performance. Group work also enhanced social and cognitive development of the students. This study provides insights into the use of self assessment in writing class to develop learner autonomy and improve writing ability.